Sequence of events from the onset to the demise of the Last Interglacial: Evaluating strengths and limitations of chronologies used in climatic archives. (1st December 2015) - Govin, A.; Capron, E.; Tzedakis, P.C.; Verheyden, S.; Ghaleb, B.; Hillaire-Marcel, C.; St-Onge, G.; Stoner, J.S.; Bassinot, F.; Bazin, L.; Blunier, T.; Combourieu-Nebout, N.; et al.
Abstract: The Last Interglacial (LIG) represents an invaluable case study to investigate the response of components of the Earth system to global warming. However, the scarcity of absolute age constraints in most archives leads to extensive use of various stratigraphic alignments to different reference chronologies. This feature sets limitations to the accuracy of the stratigraphic assignment of the climatic sequence of events across the globe during the LIG. Here, we review the strengths and limitations of the methods that are commonly used to date or develop chronologies in various climatic archives for the time span (∼140–100 ka) encompassing the penultimate deglaciation, the LIG and the glacial inception. Climatic hypotheses underlying record alignment strategies and the interpretation of tracers are explicitly described. Quantitative estimates of the associated absolute and relative age uncertainties are provided. Recommendations are subsequently formulated on how best to define absolute and relative chronologies. Future climato-stratigraphic alignments should provide (1) a clear statement of climate hypotheses involved, (2) a detailed understanding of environmental parameters controlling selected tracers and (3) a careful evaluation of the synchronicity of aligned paleoclimatic records. We underscore the need to (1) systematically report quantitative estimates of relative and absolute age uncertainties, (2) assess the coherence of chronologies when comparing different records, and (3) integrate these uncertainties in paleoclimatic interpretations and comparisons with climate simulations. Finally, we provide a sequence of major climatic events with associated age uncertainties for the period 140–105 ka, which should serve as a new benchmark to disentangle mechanisms of the Earth system's response to orbital forcing and evaluate transient climate simulations. Highlights: Review of methods to date climatic archives across the Last Interglacial (LIG). Careful evaluation of climate hypotheses underlying record alignment methods. Systematic and quantitative estimates of age uncertainties. First sequence of events with age uncertainties between 140 and 105 ka. The lack of LIG age markers limits studies of LIG millennial-scale variability.